2020
DOI: 10.1007/s13753-020-00262-1
|View full text |Cite
|
Sign up to set email alerts
|

“What is a Sociologist Doing Here?” An Unconventional People-Centered Approach to Improve Warning Implementation in the Sendai Framework for Disaster Risk Reduction

Abstract: The Sendai Framework for Disaster Risk Reduction 2015-2030 recommends several actions for early warning systems (EWSs). However, there is a lack of information about their means of implementation. This article used institutional ethnography to analyze the 2012-2018 implementation of a national warning system in Brazil. The challenges related to daily activities, and the interdisciplinary works in the four axes of EWSs towards multi-hazard and people-centered approaches are discussed. This national experience i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 59 publications
0
17
1
Order By: Relevance
“…The lack of meteorological data capture platforms or networks could also contribute to less effective early warning systems at national levels. It is suggested that the Africa Union Commission, through the RECs, implement measures aimed at better use and integration of early warning systems (see also Marchezini 2020). Data on the accessibility of these systems by the broader public is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of meteorological data capture platforms or networks could also contribute to less effective early warning systems at national levels. It is suggested that the Africa Union Commission, through the RECs, implement measures aimed at better use and integration of early warning systems (see also Marchezini 2020). Data on the accessibility of these systems by the broader public is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-two percent of countries reported that they have some form of multi-hazard early warning system(s) (MHEWS) in place. Challenges identified relate to the lack of systems integration, multiple early warning systems at various levels and in different sectors that are not coordinated, and national sovereignty issues in relation to cross-border early warnings and systems (also see Marchezini 2020). In general, the number of early warning systems has increased since 2015.…”
Section: Sendai Framework Target (G): Increase the Availability Of Anmentioning
confidence: 99%
“…PCEWSs first gained major attention after the Indian Ocean tsunami on 26 December 2004, UN ISDR(2005,2006) strongly recommended to build a national PCEWSs [ 6 , 8 ], the Sendai framework acknowledges the need for the participation of citizens and nonprofessionals when dealing with multiple hazards [ 9 ]. Putting people first is the key message of the “first mile” approach [ 10 ], which means that the system places the affected people at center stage and recognizes their role in reducing their vulnerability to the hazards they face. It is meaningful to transfer responsibility to communities and to widely encourage citizens to participate in both disseminating and responding to disaster information in “at-risk” communities, as shown by the Hyogo Framework for Action [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, form perspective of human factors, risk perception and communications [ 30 ] and response capability [ 27 ] are important in PCEWSs. However, both the UN ISDR and existing studies fail to discuss the basic characteristics of PCEWSs, how a PCEWSs should be built, and the extensible applications of PCEWSs [ 10 , 21 , 31 , 32 ]. Therefore, this study aims for making a significant contribution to the literature through the analysis of the PCEWSs trajectory of and fundamental shifts in policy pertaining to PCEWSs in the disaster domain in China.…”
Section: Introductionmentioning
confidence: 99%
“…""What is a Sociologist Doing Here?"" An Unconventional People-Centered Approach to Improve Warning Implementation in the Sendai Framework for Disaster Risk ReductionMarchezini (2020) uses institutional ethnography to analyze the 2012-2018 implementation of Brazil's national warning system. The Sendai Framework for Disaster Risk ReductionJournal of Public Administration and GovernanceISSN 2161-7104 2020…”
mentioning
confidence: 99%